POTENSI PEMANFAATAN ARTIFICIAL INTELLIGENCE UNTUK PROMOSI PARIWISATA BERBASIS KOMUNITAS: PELUANG DAN TANTANGAN REPRESENTASI BUDAYA PADA DESA WISATA DOKAN - Anis Hamidati; Feronika Berutu (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This study explores the potential use of artificial intelligence (AI) for community-based tourism promotion through a community engagement program conducted in Dokan Tourism Village, North Sumatra. A case study approach was employed, with data collected through participant observation, digital artifact documentation, descriptive pretest-posttest assessments, feedback questionnaires, and informal discussions throughout the program. A total of 17 participants, including members of the tourism awareness group (Pokdarwis), youth organization members, cultural practitioners, and traditional musical instrument artisans, participated in AI training for tourism content production.The findings indicate that AI has the potential to expand community digital participation in tourism promotion, particularly through the creation of promotional visuals using simple prompts on mobile devices. Pretest-posttest results showed improvements in participants’ understanding of AI for cultural storytelling (1.41 to 2.75), the role of communication technology in tourism promotion (1.53 to 2.58), their ability to explain Dokan Village culture to visitors (1.47 to 2.33), and their understanding of how to communicate local culture to tourists (1.94 to 2.33). However, the study also found that AI has limitations in representing local culture contextually and tends to generate more generic cultural representations that differ from authentic Karo culture. The academic contribution of this study lies in extending discussions on AI in community-based tourism by demonstrating how local communities act as cultural interpretation mediators when evaluating AI-generated outputs, while also identifying the phenomenon of cultural flattening in local cultural representation. Practically, the findings suggest that the use of AI for tourism promotion and cultural preservation should be accompanied by critical AI literacy, context-sensitive prompt development skills, and the active involvement of local communities to ensure culturally accurate representations within digital communication ecosystems.